MANIFESTAÇÕES PSICOSSOMÁTICAS EM UNIVERSITÁRIOS PORTUGUESES, A PARTIR DA IDENTIFICAÇÃO DE SINTOMAS DE ANSIEDADE, DEPRESSÃO E STRESS - Zampieri, Renata Cambiano (2013)
The present study aimed to investigate the presence of psychosomatic manifestations in college students, from the identification and prevalence of symptoms of anxiety, depression and stress disorders; to identify signs and symptoms of anxiety, depression and stress in Portuguese university students; and correlating signs and symptoms each other. As a means of research, three instruments were used: The Trait Anxiety Inventory-State Spilberber - STAI, Scale Anxiety, Depression and Stress - EADS-21 (DASS) and the Inventory of Stress Symptoms by Lipp - ISSL. The sample resulted in 147 university first entered university aged between 18 and 26 years old at the University of Algarve - Ualg (Portugal), in their various courses. The data were analyzed and correlated with the help of SPSS - Statistical Package for Social Science (SPSS) version 19.0 for Windows, using the descriptive statistical analysis of frequency and average, Student s T-test, and ANOVA. The results showed a sample of mostly women, unmarried, who left the parental home to study and at the time of the collection of the data, did not perform work activities, only studied. There was presence of indicators of anxiety, depression and stress, and anxiety level found "moderate" and linked to the likelihood of associated depression. In relation to psychosomatic manifestations, it was identified some difficulty in self-assessment of the presence of these, however it is understood that there is an association of psychosomatic manifestations in relation to symptoms of stress, anxiety and depression found. A hypothesis was raised about the association of these symptoms with the current situation of "economic crisis" that the Portuguese society is facing, especially during the collection of such data. Thus, there is a possible state of vulnerability in this population with some difficulty in adapting to the new demands of life, then requiring preventative measures to assist adaptation and restructuring of the lifestyle of these students.